Pembuatan Sistem Informasi Akuntasi Manufaktur UD.Aneka Karunia - Oscar, Timothy; Setiawan, Alexander; Setiabudi, Andy (Jurnal Infra, 2015)
UD. Aneka Karunia is a private company running in shoes accessories manufacturing located in Gedangan, Sidoarjo. It is business process consist of sales, purchasing and manufacture without good integrated system. The company only has a conventional accounting system that using Microsoft Excel. As conclusion, this system can only be used because it could save the temporary stock but could not save the flow of goods. Therefore, UD. Aneka Karunia needs an accounting information system that accommodates journal entries, production cost calculation, and financial statement.Based on this background, we designed a structural manufacture accounting information system. This system was built using Microsoft Visual Studio 2010 and MySQL.The result obtained from the system are master recording, purchase and sale transaction recording, production recording integrated with inventory card, cost of goods sold calculation and financial statement.